Experience in using ceretone (choline alfoscerate) in brain concussion - N. G. Voropay; O. B. Doronina; B. M. Doronin (Неврология, нейропсихиатрия, психосоматика)
Nootropics are used to treat patients who have sustained concussion of the brain and complain of reductions in memory and working capacity, as well as emotional disorders. The efficacy of ceretone® (choline alfoscerate) was studied in 76 patients (45 men and 31 women whose age was 21-56 years) who had sustained brain concussion and had complaints of headache, easy fatigability, nocturnal sleep disorders, daytime sleepiness, anxiety, and bad mood. Thirty-nine patients received intravenous ceretone® in a dose of 1000 mg/day for 10 days; the other 37 patients formed a control group. A one-year follow-up indicated that ceretone® had a positive effect on health, autonomic, and emotional status and working capacity.